The Pattern of Multilevel Coordination National Border Management Agency (Nbma) in Border Management Effectively in Indonesia - ., Rusdiyanta; ., Rusdiyanta; Pujiyono, Bambang (Journal of Ecohumanism, 2024)
The purpose of this study is to describe the pattern of vertical and horizontal coordination of the National Border Management Agency (NBMA) and efforts to increase the effectiveness of the coordination of the NBMA. This research uses a qualitative approach with an analytical descriptive type. The research locations are NBMA and Province/District BMA. Primary and secondary data collection in the period 2019 – 2023. The data collection technique by library research and interviews. Informants were determined purposively from elements of the central government, the provincial government, and the district government. The research focus is coordination vertically and horizontally, supporting factors, efforts to increase coordination effectiveness, and multilevel coordination models. The results of this research illustrate that NBMA coordination in border management includes coordination in determining program policies, budget requirements, and implementation coordination, such as monitoring and evaluation. Some causes of weak coordination are authority, ego sector, geographical, communication, mindset, policy, and institutional factors. Institutionally, from central to local, each institution coordinates horizontally, resulting in the complexity of vertical coordination between agencies. This condition has an impact on NBMA’s performance in managing the border. For border management to achieve its goals, good coordination is required. Efforts to increase the effectiveness of NBMA coordination are carried out through regulatory reform, reengineering, interdependence systems, and strong political support. The multilevel institutional coordination pattern is a novelty in this research and can be implemented for coordination effectively.